Induction and Conduction Electromagnetic Waves Caused by Lightning Strike on the Low Voltage Network - Zoro, Reynaldo (UI Scholars Hub, 2009)
Induction and Conduction Electromagnetic Waves Caused by Lightning Strike on the Low Voltage Network. Direct and indirect lightning strikes can disturb and induce low voltage overheadlines and it can produced overvoltage due to traveling waves along the lines. This overvoltage can damage the equipments connected to it. It was recorded that there were already a lot of damages of electronic equipments and arrestesr located inside the building of Lightning Measurement Station at Mnt. Tangkuban Perahu. Most of the overvoltage which was developed on the low voltage lines were coming from indirect lightning strike nearby due to the fact that most of the lines were covered by trees. Research was carried out to study and evaluate the induction and conduction of the lightning strikes to the LV lines that can lead to the cause of equipment and arrester damages inside the building. Local lightning data for the analysis were derived from measurement system installed at the stations and historical lightning data from lightning detection network called Jadpen (National Lightning Detection Network). The data was used for calculating and evaluating the voltage elevation, induction voltage profiles and conduction in the form of traveling waves using Rusck Model. Two damaged arresters were evaluated and compared and it give the better understanding on how the protection system work.